Interferon Beta-1a Improves Urinary Symptoms, Reduces Proviral Load, and Modifies the Immune Response in a Patient with HAM/TSP. (16th August 2012) - Costa, Davi Tanajura; Sundberg, Michael; Passos, Lúcia; Muniz, André Luiz; Santos, Silvane
Abstract : The human T-cell lymphotropic virus type 1 (HTLV-1) is the known causative agent of a chronic neurologic condition known as HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). Although several therapies have been evaluated for HAM/TSP, none have been approved for use in humans. In this paper, we describe a 55-year-old female patient with HAM/TSP who was treated with interferon beta-1a. This patient, in comparison to 20 female patients with HAM/TSP who were not treated, showed improvement in urinary symptoms over four years of therapy, as well as a reduction in HTLV-1 proviral load and serum cytokine levels typically observed in HAM/TSP. This improved outcome merits further controlled studies on the use and efficacy of interferon beta-1a as a therapy for HAM/TSP.